Bach, Maria. Relocating Development Economics: The First Generation of Modern Indian Economists - Thomas, Alex M. (Journal of Economic Literature, 2026)
Alex M. Thomas of School of Arts and Sciences, Azim Premji University reviews “Relocating Development Economics: The First Generation of Modern Indian Economists” by Maria Bach. The Econlit abstract of this book begins: “Explores the work of the Early Nationalists, the first generation of modern economists in India in the mid- to late-nineteenth century, focusing on how they produced forward-thinking knowledge on economic development.”